The Unlikely Barrèsian Inheritance of Albert Camus - Churchill, Christopher (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
This essay examines the considerable intellectual debt left-wing Albert Camus owed to one of the most unlikely of sources: far-right intellectual Maurice Barrès. Before achieving fame in France as an existential writer, he developed as a settler intellectual in colonial Algeria. The far-right exerted a profound influence on settler intellectual communities in Algeria. Many of Camus’s colleagues and friends were deeply inspired by Barrès. He was as well. Examining Camus’s complex intellectual debts to Barrès requires both a contextualization of his development as an intellectual in both Algeria and France, as well as a textual analysis of what he indeed assimilated from this icon of the far right. Camus’s attempts to wed Barrèssian fantasies of collective solidarization to his liberal political commitments risked leaving him at an impasse; however, wedding these sometimes conflicting approaches also allowed for a much broader engagement with his texts from a variety of political positions. As he confided to his mentor Jean Grenier: “I like my ideas on the left and my men on the right.”